2019
DOI: 10.2340/00015555-3144
|View full text |Cite
|
Sign up to set email alerts
|

Topical Steroid Withdrawal: A Case Series of 10 Children

Abstract: SIGNIFICANCETopical steroid withdrawal is discussed widely in social media, and some patients with a history of long-term topical steroid use are self-diagnosing this condition. There is little information in medical literature about what happens when chronic topical steroid therapy is stopped, especially in children. This study followed 10 children for between 18 months and 4 years after their parents decided to cease their topical steroid use. The children experienced typical topical steroid withdrawal sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Risk factors like topical steroid use, atopic dermatitis, disease in family, and contact with pets are known to complicate and prolong the course of dermatophytosis, alter the clinical morphology of tinea lesions, and develop dermatoses unrelated to fungal infection. [ 8 9 10 11 12 16 17 24 ] In the present study, risk factors observed were topical steroid use, disease in family members, atopic dermatitis, and contact with pets. In the patients with recurrent lesions, 66.66% were fungal test negative (developed dermatoses unrelated to fungal infection) and 33.33% had a fungal infection.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Risk factors like topical steroid use, atopic dermatitis, disease in family, and contact with pets are known to complicate and prolong the course of dermatophytosis, alter the clinical morphology of tinea lesions, and develop dermatoses unrelated to fungal infection. [ 8 9 10 11 12 16 17 24 ] In the present study, risk factors observed were topical steroid use, disease in family members, atopic dermatitis, and contact with pets. In the patients with recurrent lesions, 66.66% were fungal test negative (developed dermatoses unrelated to fungal infection) and 33.33% had a fungal infection.…”
Section: Discussionmentioning
confidence: 56%
“…Recently, few researchers reported that dermatophytosis patients may develop various lesions such as complicated/drug-resistant tinea, adverse effect unique to prolonged topical steroid use (“topical steroid withdrawal syndrome”), and chronic eczema/post-traumatic eczema at the previous sites of dermatophytosis. [ 1 6 7 8 9 10 11 12 13 14 15 16 17 18 19 ] Further, it is interesting to note that researchers did not find any correlation between risk factors like fungal infection of nail and disease in family members with the chronic dermatophytic infection. [ 20 21 22 ] Hence, it is important for physician to appropriately diagnose the recurrent lesions at the treated site of dermatophytosis prior to initiating therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The genomic pathway refers to the actions of the glucocorticoid receptor and its subsequent transcriptions of genes with anti-inflammatory functions and downregulation of pro-inflammatory genes. The non-genomic pathway is responsible for the rapid effect of TCS by affecting target [12,14,23,66,68] Burning or pain [12,17,23,66] Itching [12,16,23,26,66,68] Pustulation or Acneiform lesions [12,30] Vesiculation [12,66] Desquamation and skin shedding [23,26,66] Lymphadenopathy [23,66] Red sleeve sign Erythematous rash ending abruptly at the dorsal and palmar border, sparing the palms and soles [11,15,16,23,66]…”
Section: Pathogenesismentioning
confidence: 99%
“…The rationale proposed for an immediate cessation without a taper is that the vasoconstrictive properties of TCS contributing to TSA/TSW would still remain despite a lower potency [12]. General measures recommended during the withdrawal phase include lifestyle modifications such as dietary changes and stress control [12], psychological support [12,15,18], cold water and ice [12,66], systemic antibiotics and astringents to prevent and treat concomitant bacterial infection [12,15], analgesics [12] sedatives [12] antihistamines [66], anxiolytics [12], and oatmeal-containing bath products [12]. Other treatments tried include topical calcineurin inhibitors [67], crisaborole [67], phototherapy [67], cyclosporin [12,67], and dupilumab [67].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation